Aromatase overexpression in dysfunctional adipose tissue links obesity to postmenopausal breast cancer. Issue 153 (September 2015) - Wang, Xuyi; Simpson, Evan R.; Brown, Kristy A.
Highlights: Obesity-associated dysfunctional adipose tissue promotes postmenopausal breast cancer. Adipose tissue secretes pro-tumorigenic factors that induce oestrogen production. Aromatase is overexpressed in obesity and postmenopausal breast cancer. Inhibition of aromatases reduces estrogen production and breast cancer risk. Abstract: The number of breast cancer cases has increased in the last a few decades and this is believed to be associated with the increased prevalence of obesity worldwide. The risk of breast cancer increases with age beyond menopause and the relationship between obesity and the risk of breast cancer in postmenopausal women is well established. The majority of postmenopausal breast cancers are estrogen receptor (ER) positive and estrogens produced in the adipose tissue promotes tumor formation. Obesity results in the secretion of inflammatory factors that stimulate the expression of the aromatase enzyme, which converts androgens into estrogens in the adipose tissue. Evidence demonstrating a link between obesity and breast cancer has led to the investigation of metabolic pathways as novel regulators of estrogen production, including pathways that can be targeted to inhibit aromatase specifically within the breast. This review aims to present some of the key findings in this regard.